Interseeding lespedeza into crabgrass pasture versus additional nitrogen fertilization on forage production and cattle performance - Lomas, Lyle W.; Moyer, Joseph L.; Brazle, F.K.; Kilgore, Gary L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 160 steers grazed ‘Red River’ crabgrass pastures that were either fertilized with additional nitrogen (N) or interseeded with lespedeza during the summers of 1998, 1999, 2000, and 2001. Wheat was also grazed in 1999, 2000, and 2001 prior to crabgrass emergence. Legume cover, forage dry matter production, grazing steer performance, and subsequent feedlot performance were measured. Available forage dry matter and grazing steer performance were similar between pastures of crabgrass fertilized with additional N and those interseeded with lespedeza in 1998, 1999, and 2000. In 1999, finishing feed intake, finishing gain and ribeye area were higher (P<0.05) for steers that grazed pastures with lespedeza. In 2001, wheat grazing gain, overall grazing performance, finishing gain, and overall performance (grazing + finishing) were higher (P<0.05) for steers that grazed pastures fertilized with additional N. Total grazing gain per acre (wheat + crabgrass) was similar between pastures fertilized with additional N and those interseeded with lespedeza and averaged 304, 452, and 406 lb/acre in 1999, 2000, and 2001, respectively. In conclusion, the crabgrass wheat double-crop system produced satisfactory cattle performance with grazing gains being similar (P>0.05) between pastures fertilized with additional N and those interseeded with lespedeza. Therefore, economics rather than cattle performance would likely determine which option a producer might select. This study will be continued for three additional grazing seasons with no additional crabgrass being seeded to determine whether crabgrass will voluntarily re-seed itself sufficiently to sustain the system.
Keywords: Beef; Interseeding lespedeza; Interseeded; Crabgrass pasture; Nitrogen fertilization; Forage production; Cattle performance